2016
DOI: 10.1186/s12912-016-0169-z
|View full text |Cite
|
Sign up to set email alerts
|

Rationing of nursing care interventions and its association with nurse-reported outcomes in the neonatal intensive care unit: a cross-sectional survey

Abstract: BackgroundEvidence internationally suggests that staffing constraints and non-supportive work environments result in the rationing of nursing interventions (that is, limiting or omitting interventions for particular patients), which in turn may influence patient outcomes. In the neonatal intensive care unit (NICU), preliminary studies have found that discharge preparation and infant comfort care are among the most frequently rationed nursing interventions. However, it is unknown if the rationing of discharge p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 42 publications
4
42
1
2
Order By: Relevance
“…The current study revealed that more than one third of the NICU nurses were competent regarding care of neonates upon discharge from the NICU, and less than one fifth provided family education regarding baby discharge, this could have been related to the nurses' workload with neonates and nursing staff shortages. These results were in contradiction with those of Rochefort et al (2016), in the study entitled "Rationing of nursing care interventions and its association with nurse-reported outcomes in the neonatal intensive care unit: a crosssectional survey", where from a total of 285 NICU RNs, more than one third reported rationing discharge preparation for the neonates from the NICU competently, also they were able to provide infant comfort care in addition to being competent regarding providing the infant's relatives with the essential information for the care and follow up of their neonate after discharge.…”
Section: Discussioncontrasting
confidence: 95%
“…The current study revealed that more than one third of the NICU nurses were competent regarding care of neonates upon discharge from the NICU, and less than one fifth provided family education regarding baby discharge, this could have been related to the nurses' workload with neonates and nursing staff shortages. These results were in contradiction with those of Rochefort et al (2016), in the study entitled "Rationing of nursing care interventions and its association with nurse-reported outcomes in the neonatal intensive care unit: a crosssectional survey", where from a total of 285 NICU RNs, more than one third reported rationing discharge preparation for the neonates from the NICU competently, also they were able to provide infant comfort care in addition to being competent regarding providing the infant's relatives with the essential information for the care and follow up of their neonate after discharge.…”
Section: Discussioncontrasting
confidence: 95%
“…These four activities have the most direct impact on family-centered care, as compared to physical elements of care such as skin care or treatments and procedures. These results are consistent with evidence from province-wide samples of Quebec NICUs in 2007-2008, and in 2014, which showed that the most frequently missed activities were discharge planning, parental support and teaching, and comfort care (16,20).…”
Section: Discussionsupporting
confidence: 89%
“…One study in a USA medical center linked delayed feeding (a type of missed care) of NICU infants to time required to achieve full oral feedings and length of stay (19). Nurses who worked in seven Quebec NICUs reported that missed discharge teaching was inversely associated with nurse-ratings of parent-infant readiness for discharge, and that missed parental support, teaching, and infant comfort care was associated with ratings of poorer pain control (20).…”
Section: Missed Nursing Carementioning
confidence: 99%
“…Rochefort and Clarke (2010) first used the NEW-RI tool to identify the nursing activities mostly rationed due to lack of time: activities related to discharge planning, parental support and teaching, and comfort care of the patients. In a newer study, Rochefort et al (2016) confirmed the previous results and added a new finding: more than half of the nurses are dissatisfied with pain relief management. We can conclude that the following activities were identified among the most frequently rationing nursing activities: the education of patients and families (Jones, 2015 The conclusion from the above mentioned results is that the differences in the individual approaches caused a considerable variability of research results aimed at monitoring the level of prevalence of this phenomenon.…”
Section: Implicit Rationing Of Care and The Bernca Pirnca And New-rmentioning
confidence: 53%